2021
DOI: 10.1038/s41598-021-81256-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional disruption of cortical cingulate activity attenuates visceral hypersensitivity and anxiety induced by acute experimental colitis

Abstract: Visceral pain is a highly complex experience and is the most common pathological feature in patients suffering from inflammatory gastrointestinal disorders. Whilst it is increasingly recognized that aberrant neural processing within the gut-brain axis plays a key role in development of neurological symptoms, the underlying mechanisms remain largely unknown. Here, we investigated the cortical activation patterns and effects of non-invasive chemogenetic suppression of cortical activity on visceral hypersensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Researchers showed that regional characteristics of neuronal activity in the PoCG was linked to depression severity (Tadayonnejad et al, 2015). In first-episode MDD patients, researchers discovered greater local efficiency of the right PCL when compared to HCs (Chen et al, 2022). Furthermore, stronger PCL-amygdala resting-state FC has been reported in mood disorders with suicidal behavior (Zhang R. et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers showed that regional characteristics of neuronal activity in the PoCG was linked to depression severity (Tadayonnejad et al, 2015). In first-episode MDD patients, researchers discovered greater local efficiency of the right PCL when compared to HCs (Chen et al, 2022). Furthermore, stronger PCL-amygdala resting-state FC has been reported in mood disorders with suicidal behavior (Zhang R. et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the right MCC decreased ReHo after taVNS was significantly positively correlated with the decreased of HAMD scores. The MCC has been linked to cognitive regulation, negative affect processing, and pain processing ( Wong et al, 2019 ; Brenner et al, 2021 ). Decreased functional connectivity (FC) between the MCC and other brain areas was attributed to decreased depression after antidepressant medication ( Tan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…While there are no commercial comparisons to the VPS, there are reports in the literature of other custom units [13][14][15] or methods of pressure reading and recording [16,17]. To our knowledge, none of these other units are described in detail preventing a clear comparison of advantages and disadvantages to the VPS.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the effect is mutual; several studies have found that irritability, anxiety, and other psychological effects of long-term stimulation can make the central nervous system (CNS)—including the anterior cingulate gyrus, amygdala, insula, hypothalamus, prefrontal cortex, and other brain areas—show abnormal activation, thereby aggravating the degree of VH [ 12 , 13 ]. Mechanical stimulation of the colon results in persistent hyperactivation of the middle cingulate cortex; in acute colitis, downregulation of anterior cingulate cortex excitability successfully attenuates visceral hypersensitivity, anxiety-like behaviors, and visceral motor response [ 14 ]. CNS neurons in a VH state demonstrated increased release of a variety of neurotransmitters, which are mostly encapsulated in vesicles for transport [ 15 ].…”
Section: Introductionmentioning
confidence: 99%